An Assessment of Performance of Anganwadi Workers of Jaipur Zone, Rajasthan: A Cross-Sectional Study - Dayanand Singh; Kusum Lata Gaur; Dilip Raj; Amita Kashyap; Rashmi Gupta; Anuradha Yadav (Medsci Publications, 2013)
Background: - Integrated Child Development Service (ICDS) is India's response to the challenge of meeting the holistic needs of children below six years of age, adolescent girls expectant and nursing mothers through the network of Anganwadis. Objectives: - To assess the performance of Anganwadi Workers of Jaipur Zone (Rajasthan) India. Materials and Methods:- 8 AWCs were selected from each of the 5 Zones of Jaipur. So, total 40 AWCs were included in the present survey. Performance of each of the AWW from identified AWCs was assessed as per the 'Form no. (4) to (6) of ICDS. Performance of various districts and various activities were analyzed with chi-square/ANOVA/Post-Hoc wherever applied Results: - Average mean time opening of AWCs of Jaipur zone was 18.8 minutes less than the ideal duration of 240 minutes per day. 81.67% mothers received supplementary nutrition distribution for their children of 0-3 years and 61.67% for themselves. 67.50% mothers received Vit-A doses from the AWCs for their children. 58.33% mothers received IFA syrup/tab for their children and 52.18% received IFA for themselves. But only 14.17% mothers mentioned that they had received health check-up for the children. Conclusion: - Although HNE and distribution of supplementary nutrition was observed excellent but Services for adolescent girls were not at all proper.